2018
DOI: 10.1111/jam.14074
|View full text |Cite
|
Sign up to set email alerts
|

Gluconacin fromGluconacetobacter diazotrophicusPAL5 is an active bacteriocin against phytopathogenic and beneficial sugarcane bacteria

Abstract: The production of a recombinant protein, named Gluconacin, opens new avenues for the agro-biotechnology application in agriculture, mainly with regard to the sugarcane crop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Various antimicrobial compounds secreted by bacterial strains can exert bene cial effects in sustaining plant health. For example, the role of bacteriocin produced by endophytic bacteria as a source of new antibacterial compounds have synergistically been employed to upsurge antibiotic resistance (Lopes et al 2017;Oliveira et al 2018). Organic compounds synthesized by bacteria naturally play a vital role in the adaptation and survival of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Various antimicrobial compounds secreted by bacterial strains can exert bene cial effects in sustaining plant health. For example, the role of bacteriocin produced by endophytic bacteria as a source of new antibacterial compounds have synergistically been employed to upsurge antibiotic resistance (Lopes et al 2017;Oliveira et al 2018). Organic compounds synthesized by bacteria naturally play a vital role in the adaptation and survival of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…The ICMP196 strain of X. albilineans, used as a model microorganism for the evaluation of bacteriocin activity, was obtained from the Collection of Phytopathogenic Bacteria of the Biological Institute of São Paulo. Culture media and growth conditions as well as the protocol used for recombinant Gluconacin expression have been described in our previous studies (Oliveira et al, 2018). Bacterial growth and recombinant Gluconacin expression were evaluated under the following incubation temperatures: 16, 25, 30 and 37 C. After the time of induction of protein expression (4 h), 3 ml of bacterial cultures were centrifuged (10,000g for 15 min), the supernatant discarded and the pellet resuspended in 300 μl of lysis buffer (50 mmol L À1 KH 2 PO 4 and K 2 HPO 4 , 400 mmol L À1 NaCl, 100 mmol L À1 KCl, 10% glycerol, 0.5% Triton X-100, pH 7.4).…”
Section: Microorganisms Growth Conditions and Gluconacin Expression In E Coli Bl21-aimentioning
confidence: 99%
“…Our team have cloned and demonstrated the heterologous expression of the GDI0415 gene, coding for Gluconacin, a bacteriocin produced by diazotrophic G. diazotrophicus PAL5. It has previously been demonstrated that this proteinaceous molecule has wide inhibitory activity against Gramnegative and Gram-positive bacteria, including the main causative agents of diseases of economic importance for large crops, such as sugarcane (Oliveira et al, 2018). However, this antimicrobial peptide has neither been characterised nor its mode of action elucidated, despite the fact that several bacteriocin-like compounds have been detected in G. diazotrophicus PAL5 (Blanco, Blanch, Piñ on, Legaz, & Vicente, 2005;Muñoz-Rojas, Fuentes-Ramirez, & Caballero-Mellado, 2005;Piñ on et al, 2002).…”
mentioning
confidence: 99%
“…Specific PCR primers were designed for the wzc gene (GDI2549) from G. diazotrophicus strain Pal5 and the MGD and MWzc mutants (Table 1). The E. coli expression system with Gateway ® technology (Thermo Fisher Scientific, Waltham, MA, USA) was applied to express the Wzc heterologous protein in E. coli strain BL21-AI™ using the suitable plasmids [34,35] and quantified [36]. The functionality of Wzc in different strains from G. diazotrophicus was tested by using heterologous expression in E. coli strain BL21-AI™.…”
Section: Cloning and Expression Of The Wzc Gene In E Coli Strain Bl21-aimentioning
confidence: 99%